Clinical Use of the Low-Molecular-Weight Heparins in Cancer Patients: Focus on the Improved Patient Outcomes. (27th March 2011) - Chao, Bo H.; Lepeak, Lisa; Leal, Ticiana; Robins, H. Ian
Abstract : Patients with malignant neoplastic diseases represent a high-risk population relative to thromboembolic disease. With the advent of improved and accessible diagnostic technology, for example, ultrasound and/or spiral CT scans, timely diagnosis of venous thromboembolic events (VTE) is readily accomplished. The introduction of low-molecular-weight heparin (LMWH) approximately two decades ago (in contrast to unfractionated heparin and vitamin K antagonists) has provided a class of agents with a favorable therapeutic index. In the review to follow, the literature regarding the use of LMWH in oncologic patient populations is summarized. Topics addressed include prophylaxis, and treatment as well as consideration of the potential anti-neoplastic properties of this class of drugs.